Spatial and Temporal Characteristics of Personal Self-Realization in Vocational Educational Environment: Theoretical Methodological Prerequisites - D. P. Zavodtchikov (Образование и наука)
The paper considers the current concepts of human subject as a theoretical methodological basis for exploring the spatial and temporal characteristics of personal self-fulfillment in vocational educational environment. The human subject is regarded as a system capable of cognition and conversion of other systems in accordance with the personal logic of functioning and development. The author defines the psychological concept of human subject referring to the indeterminism theory and inner development logic, and broadens the above concept applying the categories of limitations and limitlessness as a combination of realizable and potential aspects. The methodological bases and existing theoretical concepts of the human subject are given. The main objective involves realization of his temporal and spatial organization. The paper summarizes the ideas of space and time in social and psychological sciences. The categories of self-development and self-fulfillment in psychological time and space are based on the dual subjective perception – i.e. continuity/discreteness, infinity/finiteness. The spatial and temporal characteristics of human existence and self-fulfillment are denoted.